Dormant season warming amplifies daytime CO2 emissions from a temperate urban salt marsh - Vieillard, Amanda M.; Girguis, Peter; Fulweiler, Robinson W. (Frontiers in Environmental Science, 2024)
Salt marshes provide many ecosystem services, key among them being carbon sequestration. However, a large degree of uncertainty remains in salt marsh carbon budgets, particularly during colder months of the year when salt marsh microbial and vegetative activity is assumed to dormant. We also lack data on urban systems. In this study, we used an easily portable carbon dioxide sensor package to directly measure net carbon dioxide (CO2) fluxes throughout the winter in a temperate, urban salt marsh. We sampled across the dormant season both on normal (cold) temperature days and on days that were anomalously warm (defined here as air temperatures 2.8 °C above the long-term average). We demonstrated that median (±mad) daytime CO2 fluxes doubled on the warm days, compared to cold days (1.7 ±2 mmol m-2 h-1, 0.7 ±1.3 mmol m-2 h-1, respectively). We also show that net CO2 emissions scaled with soil temperature. The high day-to-day variability, however, implies that infrequent or sparse measurements cannot sufficiently capture the temporal dynamics of dormant season salt marsh net CO2 fluxes. The magnitude of the net CO2 source from our sampling during the dormant season leads us to hypothesize that, as mean annual temperatures continue to increase, dormant season CO2 emissions from salt marshes will increasingly offset growing season carbon dioxide uptake. This change compromises the carbon sequestration capacity, and therefore the climate mitigation potential of these ecosystems. Future studies should focus on quantifying the impact of dormant season CO2, and other greenhouse gases on salt marsh carbon budgets.